The encyclopedia of epic films - Santas, Constantine; Wilson, James M. 1959-; Colavito, Maria Maddalena; Baker, Djoymi 1972- (Rowman & Littlefield, 2014)
Soon after film came into existence, the term epic was used to describe productions that were lengthy, spectacular, live with action, and often filmed in exotic locales with large casts and staggering budgets. Although the form has evolved over the decades, its central elements have been retained. This text analyzes films that meet the criteria of the epic-- from D.W. Griffith to Steven Spielberg, as well as foreign and television epics